The Effectiveness of the Culturally Responsive Teaching Approach on the Structure of Observation Report Texts in Indonesian Language Learning in Class VIII C of SMP Negeri 1 Kota Cirebon - opi_sopiah0311 (Universitas Swadaya Gunung Jati, 2024)
This study aims to evaluate the effectiveness of the Culturally Responsive Teaching (CRT) approach in enhancing students' understanding of the structure of observation report texts by integrating elements of local culture and students’ personal experiences into the learning process. This research employed a quantitative pre-experimental design, conducted through two stages of data collection: a pre-test and a post-test. The sample consisted of 49 eighth-grade students from Class VIII C at SMP Negeri 1 Kota Cirebon. The data collected focused on cognitive learning outcomes. In this study, a normalized gain (N-Gain) test was used to determine the improvement in students’ average pre-test and post-test scores. The results showed an N-Gain score of 0.72, indicating that students fell into the “high” category and achieved significantly better cognitive learning outcomes